Alport syndrome: impact of digenic inheritance in patients management. Issue 1 (22nd February 2017) - Fallerini, C.; Baldassarri, M.; Trevisson, E.; Morbidoni, V.; La Manna, A.; Lazzarin, R.; Pasini, A.; Barbano, G.; Pinciaroli, A.R.; Garosi, G.; Frullanti, E.; Pinto, A.M.; et al.
Abstract : Alport syndrome (ATS) is a genetically heterogeneous nephropathy with considerable phenotypic variability and different transmission patterns, including monogenic (X‐linked/autosomal) and digenic inheritance (DI). Here we present a new series of families with DI and we discuss the consequences for genetic counseling and risk assessment. Out of five families harboring variants in more than one COL4 gene detected by next generation sequencing (NGS), minigene‐splicing assay allowed us to identify four as true digenic. Two families showed COL4A3/A4 mutations in cis, mimicking an autosomal dominant inheritance with a more severe phenotype and one showed COL4A3/A4 mutations in trans, mimicking an autosomal recessive inheritance with a less severe phenotype. In a fourth family, a de novo mutation ( COL4A5 ) combined with an inherited mutation ( COL4A3 ) triggered a more severe phenotype. A fifth family, predicted digenic on the basis of silico tools, rather showed monogenic X‐linked inheritance due to a hypomorphic mutation, in accordance with a milder phenotype. In conclusion, this study highlights the impact of DI in ATS and explains the associated atypical presentations. More complex inheritance should be therefore considered when reviewing prognosis and recurrence risks. On the other side, these findings emphasize the importance to accompany NGS with splicing assays in order to avoid erroneous identification of at risk members. Abstract :